Identification of a common molecular pathway in hypertensive renal damage: comparison of rat and human gene expression profiles. Issue 3 (March 2015) - Skogstrand, Trude; Leh, Sabine; McClure, John; Dashti, Mohammed; Iversen, Bjarne M.; Graham, Delyth; McBride, Martin W.; Hultström, Michael
Abstract : Background: There is a common structural progression in hypertensive renal damage with early arterial damage and fibrosis in the juxtamedullary cortex. Method: The present investigation identifies a common pathway using three-gene expression profiles from hypertensive rat models: 60-week-old spontaneously hypertensive rat (SHR), salt-loaded stroke-prone SHR (SHRSP), and the non-clipped kidney after 24 weeks of two-kidney, one-clip hypertension (2K1C). Kidney damage was scored using a specialized system. Gene-expression profiles were determined using microarrays and validated using a panel of 47 genes by quantitative real-time PCR. Results: All groups showed kidney damage (SHRs: 0.32 ± 0.09 vs. Wistar–Kyoto rats: 0.06 ± 0.03; 2K1C: 0.27 ± 0.13 vs. pooled controls: 0.01 ± 0.01; SHRSP: 1.13 ± 0.14 vs. WKY: 0.04 ± 0.03; all P < 0.05). A total of 1614 genes were changed in the SHR experiment, 1323 in the SHRSP, and 576 in the 2K1C. Eighty-eight genes were similarly regulated in all three models. Gene ontology enrichment analysis identified 59 ontologies that were enriched in all three datasets. These included over-representation to extracellular matrix, response to oxidative stress, and immune system processes. Out of the 88 in-common genes, 40 could be connected in a common pathway that was compared to two gene-expression profiles from human kidneys with histologically verified fibrosis to identify a highly significant number of in-common genes that were also represented in the common genetic pathway. Conclusion: There is a common pathway during the development of hypertensive kidney damage in rats irrespective of model. Interestingly, large parts of this common pathway are conserved in human kidney damage, which may indicate a broader importance in the development of chronic kidney disease. Abstract : Supplemental Digital Content is available in the text